2009
DOI: 10.1177/0016986208330564
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Representation in Gifted Programs

Abstract: The Elementary and Secondary School Survey data and Civil Rights Data Collection of the Office for Civil Rights (OCR) were analyzed to describe the issue of overrepresentation of gifted Asian American students in gifted education programs in the United States. Nationally, Asian and Whites have been overrepresented in gifted education since 1978, whereas, students from other ethnic backgrounds, such as those from American Indian or Alaska Native, Hispanic, and African American groups, have been underrepresented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
82
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 36 publications
(58 reference statements)
9
82
4
1
Order By: Relevance
“…Thus, before children even enter school, massive differences in OTL already exist. These early inequalities contribute to the observed score differences shown in Tables 1 to 4 and in the differential rates of identification as gifted reported by Yoon and Gentry (2009). Put differently, the underrepresentation observed in gifted identification rates is, in part, a symptom of larger societal inequality.…”
Section: Introductionmentioning
confidence: 89%
“…Thus, before children even enter school, massive differences in OTL already exist. These early inequalities contribute to the observed score differences shown in Tables 1 to 4 and in the differential rates of identification as gifted reported by Yoon and Gentry (2009). Put differently, the underrepresentation observed in gifted identification rates is, in part, a symptom of larger societal inequality.…”
Section: Introductionmentioning
confidence: 89%
“…Lee, 2002), including in gifted education research (S.-Y. Lee & Olszewski-Kubilius, 2006;Olszewski-Kubilius & Lee, 2011;Yoon & Gentry, 2009). These inequalities increased as students in this study spent more time in the gifted magnet program.…”
Section: Research Question 3: Demographic Ivsmentioning
confidence: 99%
“…Hispanic students were overrepresented in 1 state, evenly represented in gifted programs in 2 states, and underrepresented in 47 states, and Black students were evenly represented in 3 states and underrepresented in 47 states. Black students were not overrepresented in gifted programs in any state in 2006 (Yoon & Gentry, 2009). Yoon and Gentry (2009) also confirmed the prevailing wisdom regarding the overrepresentation of Asian American and White students in gifted programs in the United States (e.g., Carman & Taylor, 2010) compared to the proportions that these groups are found in the general school population.…”
mentioning
confidence: 99%
“…Black students were not overrepresented in gifted programs in any state in 2006 (Yoon & Gentry, 2009). Yoon and Gentry (2009) also confirmed the prevailing wisdom regarding the overrepresentation of Asian American and White students in gifted programs in the United States (e.g., Carman & Taylor, 2010) compared to the proportions that these groups are found in the general school population. The researchers found that, in 2006, Asian Americans were disproportionately overidentified as gifted in 45 states and were proportionally identified as gifted in 5 states.…”
mentioning
confidence: 99%
See 1 more Smart Citation